Investigation the efficiency of integration microbial electrolysis cell to anaerobic digester for biomethane production - Aldaas, Aseel; Alam, Md. Zahangir; Azmi, Azlin Suhaida (2023)
The integration of Microbial electrolysis cell to anaerobic digestion has emerged as a promising solution for the upgrade of biomethane within the system. It facilitates the conversion of organic waste into biomethane without the need to CO2 capture and separation downstream processes. Recent studies have showed that modifying the electrodes has a major effect on the microbial stages, specifically hydrolysis, acidogenesis’s, which are key steps for the final stage methanogenesis. Understanding these stages in the MEC-AD system allows researchers to identify potential bottlenecks and optimize the conversion of organic matter into methane. In addition, the final stage, namely methanogenesis which is responsible for the biomethane production and upgrade, is highly affected the by the density of the methanogenic community and the diversity of the inoculum. This study investigated the effect of integrating unmodified, and modified electrodes of MEC to anaerobic digester on the two stages hydrolysis and acidogenesis, then the kinetic modelling of biomethane production with mixing two inoculums namely cow manure and effluent of a previous digester. Hybrid systems showed a higher hydrolysis efficiency especially modified systems, with a percentage of 39.4% by the 48th hour, followed by unmodified systems. The acidogenesis pathway results showed that the hybrid systems were dominated by the acetic acid pathway, which is favourable in the hybrid system, unlike the conventional digester, which was dominated by a different pathway. Mixing the original inoculum obtained from a previous AD with cow manure has enhanced and increased the competitiveness of the microbial community. Thus, it was positively reflected on the biomethane production potential and rate, with a value of 38ml/g COD and 1.2 ml/h, respectively.